Points and counterpoints in the development of interdisciplinarity in nursing technical training - Fontana, Patricia Maia; Pinto, Adriana Avanzi Marques; Marin, Maria José Sanches [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: To characterize the points and counterpoints in the development of interdisciplinarity in the nursing technical training. Method: This is an exploratorydescriptive study with a qualitative approach conducted through interviews with 30 teachers and coordinators of nursing technical courses from 12 different regions of the state of São Paulo. Data analysis was performed through theme-based content analysis. Results: Regarding the theme of institutional orientation, it was found that, although there are initiatives to promote interdisciplinarity, since there is teacher training and definition of goals for articulation with other courses and for the joint work among the teachers of the disciplines, these are still vague and ineffective. As for the theme, the implementation of interdisciplinarity by the teachers, it is observed that they seek different forms of integration, but they come across the curricular structure, the form of teacher hiring, and the resistance to changes. With respect to the comprehension of the concept, relevant aspects of its meaning are recognized; however, they admit the existence of limits. Conclusion: The institution defines a trajectory aiming at interdisciplinarity, the teachers try to follow the path for its implementation; however, they find structural obstacles, little comprehension of the concept, and resistance to changes. It appears that efforts are needed to advance the curricular implementation with the logics of interdisciplinarity.
Puntos y contrapuntos en el desarrollo de la interdisciplinariedad en la formación técnica en enfermería
Pontos e contrapontos no desenvolvimento da interdisciplinaridade na formação técnica em enfermagem
Keywords: Associate; Education; Health Human Resource Training; Interdisciplinary Placement; Nursing